(untitled) (International Journal of Built Environment and Sustainability, 2023)
Adaptive facades are widely used today because they are energy efficient and sustainable. It is expected that kinetic facades will become more common in the future and new geometries are constantly sought. Kinetic Reciprocal Frame (KRF) structures are also one of the innovative and sustainable approaches. In this study, KRF structures are used as adaptive facades and are analyzed in two stages. As a test model, a standard high-rise office building in Ankara, Turkey is created and simulations are made on the south facade. In the first stage, the modules’ applicability in different geometries is examined and the differences within the geometries are revealed. KRF modules are examined for cost-effectiveness and mobility. In the second stage, analyzes are made on the daylight performance of the geometries. Modules are evaluated based on spatial daylight autonomy (sDA), annual sunlight exposure (ASE), and average lux. As a result, in terms of daylight performance, the hexagonal KRF module gives the best result by drawing the most homogeneous values due to its high mobility. However, it is noticed that the daylight performance of the triangle KRF module is weak compared to other modules, the ASE values cannot be controlled and it is more difficult to implement because it is not effective in terms of cost per module. The fact that hexagonal modules give good results in terms of cost is found to be good in support of it. This study is also valuable study in terms of the application performance of KRF structures on the facade.